PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA MASYARAKAT USING DI KABUPATEN BANYUWANGI - Gani, Husni Abdul (FKM - UNEJ, 2013)
Clean and healthy behaviors which in Indonesia called PHBS is a embodiment of healthy paradigm on individual culture. This study aims to analyze the clean and healthy behaviors of Osing society in Kemiren village, Glagah distict, Banyuwangi. This study was an observational study which conducted in June-December 2013. The population of this study were all of families in Kemiren village, as many as 754 families. The sample of this study were 100 respondent which taken using simple random sampling methods. The analysis of the data using descriptive analysis. The results showed that the amount of respondents were men, more than 50 years old, had low level of education (elementary school) and had profesion as farmers.The behaviors of healthy latrines use is 54%, less healthy latrines use is 37%, and bad healthy latrines use is 9%. The behaviors of clean water use is 94% and not clean water use is 6%. The behaviors of respondent on using trash is 37% and not using trash is 63%. The behaviors of less healthy latrines use and the lack of using trash caused by the lack of respondents awareness on clean and healthy behaviors (PHBS). So, it needs to concerted effort on clean and healthy behaviors (PHBS) promotion. Keywords : Behaviors, PHBS, Osing society